6–18 GHz, 8.1 W size‐efficient GaN distributed amplifier MMIC. Issue 8 (1st April 2016) - Kim, J.; Park, H.; Lee, S.; Kwon, Y.
Abstract : A 6–18 GHz, 8.1 W gallium nitride (GaN) distributed amplifier (DA) monolithic microwave integrated circuit (MMIC) is presented with compact size. To accomplish high‐output power density with compact size, the last two sections of the DA consist of small‐sized FETs. This approach improves the output return loss and allows the drain line lengths to be reduced thereby increasing the drain cut‐off frequency and reducing circuit size, which results in increased gain and output power characteristics up to higher frequencies. Source via holes of GaN high electron mobility transistors (HEMTs) are also shared to reduce chip size. The proposed DA is implemented as a two‐stage DA using a commercial 0.25 µm GaN MMIC process. It shows 8.1 W average continuous wave output power and 6.8 dB average associated gain from 6 to 18 GHz under 36 V drain bias with 6.7 mm 2 chip area. The proposed DA obtains 1.21 W/mm 2 output power density and 1.02 dB/mm 2 gain density.